(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The study conducted a content analysis of four selected Nigerian daily newspapers namely; Daily Trust, Leadership, the Nation and Vanguard Newspapers in order to assess the coverage of food security and climate change issues/stories by these newspapers. The study covered a period of three years (2020, 2021 and 2022). The objectives of the study were to determine the volume of coverage of food security and climate change issues by the selected Nigerian newspapers, compare the total coverage of food security and climate change issues amongst them. The four selected newspapers were purposively chosen based on popularity in four regions, a total of 4380 issues of the 4 newspapers were obtained. Descriptive statistics was used to describe the coverage while Paired t-test was used to compare differences between the total coverage of climate change and food security issues by each newspaper. The findings of the research revealed that coverage of food security and climate change information by selected newspapers in the study area is generally low with 1,247 (31%) articles and 611 articles (15%) respectively. Leadership newspaper had the highest number of coverages with 187 issues/stories on climate change while Daily Trust had the highest coverage of food security issues/stories with 365. It was therefore recommended that the newspaper publishers should increase innovative coverage and passing of food security and climate change issues including engaging Journalist in climate summits, workshops and conferences.